Together for the greater goods: legitimising social innovation in the pharmaceutical field - Kleinhout-Vliek, T.H.; Boon, W.P.C.; Hagendijk, R.P.; Hoekman, J.; Moors, E.H.M. (Innovation (Abingdon, England), 2024)
Social innovation initiatives in the pharmaceutical field seek alternative, collaborative ways to address problems with availability and affordability of medicines. However, these experimental initiatives require legitimacy. Formulating goals is a way of creating and contesting legitimacy, also for social innovation initiatives, yet has not been studied in this context. Based on document analysis (policy reports, news articles and websites) and semi-structured interviews, we investigate what form and role goal formulations take in constructing and contesting the legitimacy of two Dutch social innovation initiatives: one novel coverage arrangement for a rare disease drug and one new manufacturing process for a personalised cancer treatment. We find that actors formulate goals to manage consensus with powerful, independent governance bodies and with those who reserve their judgement concerning the initiative. They also manage differences, highlighting role differentiation within collaborations and emphasising contrasts with outsiders. These findings show the importance of professional identities and the experimental nature of social innovation initiatives. We conclude that formulating goals is used to probe for and attempt to ensure the longevity of social innovation. Working together in diverse partnerships for 'the greater goods' (plural) is thus essential for organising durable social innovation in the European pharmaceutical field .